The North American species of the non-native flora of the Kyiv urban area (Ukraine): a checklist and analysis - Yavorska, Oksana (Biodiversity: Research and Conservation, 2010)
This paper presents an annotated checklist of the North American species established in the flora of the Kyiv urban area (KUA). For each taxon, the following data are provided: distribution in the area, degree of naturalization, period of immigration, mode of immigration and ecological characteristics. The group of the North American neophytes consists of 114 species belonging to 71 genera and 36 families and 23 cultivated species and of problematic taxonomic status. Among them prevail ergasiophytes (26%), ergasiophygophytes (22%) and ephemerophytes (19%). The majority of neophytes (47%) have spread over all types of ecotopes. Among them 12 species are invasive alien plants in the KUA.